2000
DOI: 10.1021/ic000819d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Nickel Sulfides in Aqueous Solutions Using Sodium Dithionite

Abstract: Reaction of nickel chloride with sodium dithionite in aqueous solutions at ambient temperature has been investigated systematically to obtain nickel sulfides. The products are characterized by X-ray diffraction, thermogravimetric analysis, and electrical resistivity and magnetic susceptibility measurements. It is found that the compositions and structures of the products are controlled by the reaction pH and the amount of the reactants. While reactions under highly acidic (pH < or = 2) and basic (pH > or = 7) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 29 publications
3
35
0
Order By: Relevance
“…We performed these experiments under anaerobic conditions, in the glovebox, at room temperature in 1.5 mL eppendorf tubes containing 25 to 100 µL of 0.44 µM enzyme solution in 0.1 M Tris/HCl pH 8 in the presence of exogenous nickel under reducing conditions or not, with 0 to 10 mM NiCl 2 and/or 0 to 10 mM NaDT for 1-60 min. In the solution containing both NiCl 2 and NaDT, a black precipitate formed, probably due to formation of nickel sulfides under basic conditions, as described previously [40]. A control experiment performed in the absence of enzyme showed that this precipitate has no CODH activity.…”
Section: Activation Of the Enzymesupporting
confidence: 67%
See 1 more Smart Citation
“…We performed these experiments under anaerobic conditions, in the glovebox, at room temperature in 1.5 mL eppendorf tubes containing 25 to 100 µL of 0.44 µM enzyme solution in 0.1 M Tris/HCl pH 8 in the presence of exogenous nickel under reducing conditions or not, with 0 to 10 mM NiCl 2 and/or 0 to 10 mM NaDT for 1-60 min. In the solution containing both NiCl 2 and NaDT, a black precipitate formed, probably due to formation of nickel sulfides under basic conditions, as described previously [40]. A control experiment performed in the absence of enzyme showed that this precipitate has no CODH activity.…”
Section: Activation Of the Enzymesupporting
confidence: 67%
“…We have no clear explanation for this decrease in activity. However, we have observed that during activation (ie incubation of the enzyme with NaDT and NiCl 2 ), the solution progressively turns dark, probably because of nickel sulfide formation due to reaction of NaDT with NiCl 2 , as described in Jeong et al [40]. In consequence, the NaDT and NiCl 2 concentrations decrease over time and it may be that the optimal nickel concentration and/or the reducing power required for keeping the enzyme in a fully activated state are not maintained.…”
Section: Kinetics Of Coos and Coos Csupporting
confidence: 53%
“…PEG is a dispersing agent and acts as a surfactant by adsorption at solid-liquid interfaces; forming a layer of molecules in a membrane prevents particles from being in contact with each other, reduces the surface tension and capillary adsorption capacity, and suppresses crystal growth, resulting in a small size distribution of the nanoparticles [15]. Based on these, the effects of PEG used in the synthesis of the SiO 2 -nZVI on the degradation of Malachite green were examined in this study, and the result was shown in those synthesized in the absence of PEG.…”
Section: Influence Of Peg In the Sio2-nzvi Preparation Processmentioning
confidence: 99%
“…To achieve the aforementioned morphologies several synthesis methods have been employed, such as chemical vapor deposition [16], solvothermal [10,12], mechanical alloying [17], polyol method [18], solventless synthesis [19] and so on [20].…”
Section: Introductionmentioning
confidence: 99%